Investigation of Horizontal Well for Cyclic Steam-Solvent Stimulation to Escalate Heavy Oil Production - Suranto, Ahmad Muraji; Lukmana, Allen Haryanto; Putradianto, Ristiyan Ragil; Asy'ari, M Rizqi (Journal of Earth Energy Engineering, 2022)
Indonesia's oil reserves that have been exploited on a large scale are light oil because the recovery technique is much easier than the heavy oil. Generally, heavy oil has a high viscosity compared to light oil. In most cases, to reduce high oil viscosity (greater than 50 cp) using steam injection. Cyclic steam stimulation (CSS) is one of processes that commercially developed by numerous oil company to producing of heavy oil reservoir. The CSS can apply in vertical well or horizontal well. The research of CSS in horizontal well is still limited reported in the literature. On the other hand, the horizontal well has drainage area more wide compared with vertical well. In this study, solvent addition in cyclic steam stimulation will be tested with reservoir simulation. The steam was injected on the well, after that soaking time and the last was producing of liquid fluid reservoir. As the result, the oil production increases 3 times higher compared to without solvent. Furthermore, cumulative steam oil ratio (CSOR) and cumulative energy oil ratio (CEOS) decrease about 50% and 16%, respectively. In here, effect of solvent added in the steam, the steam distribution and drainage area wider.